Possibilities of using biomass in district heating with focus on agricultural biomass as a fuel to replace coal, taking into account economic and technical aspects - Pronobis , Marek; Kalisz, Sylwester; Majcher , Jerzy; Wasylów , Józef; Sołtys , Józef (Instal, 2020)
The article discusses the possibilities of using biomass in district heating. In the power industry there is currently a strong trend of replacement of fossil fuels in favour of renewable sources, and thus more and more often the possibilities of replacing hard coal by biomass are analyzed – in this case with particular emphasis on agricultural biomass, which is a widely available fuel on the Polish market. The article also discusses the possibility of using fuel additives – halloysite, to improve the combustion process, but also by-products of combustion such as ash and slag. The impact of halloysite on selected aspects of the combustion process is shown, as well as the potential benefits of using fuel additives. The further part of the article discusses the biomass market in Poland and Europe and presents forecasts for the future use of biomass fuels as an alternative to hard coal or co-firing. The whole article was summarized with economic analysis and an analysis of potential possibilities to relieve the environment.
Keywords: alternative fuels; additives; halloysite; district heating; biomass